Participatory Forums and Influence - Dickson, John W. (Academy of Management Journal, 1982)
The article presents a study which examined whether the presence of a formal participatory body is associated with higher levels of interaction, communication to upper managers, communication from upper managers, influence from upper managers and effect on decisions. 82 lower level managers working for one of seven large business organizations in Tucson, Arizona have served as respondents of the study. The study revealed that formal forums do enhance perceptions of some component processes of participations, but perceived upper managerial influence is unaffected by the existence of participatory bodies.